A Cross-Efficiency Based Ranking Method for Finding the Most Efficient DMU. (17th April 2014) - Sadeghi Gavgani, S.; Zohrehbandian, M.
Abstract : In many applications of DEA, ranking of DMUs and finding the most efficient DMU are desirable, as reported by Toloo (2013). In this paper, after introducing an improvement to the measure of cross-efficiency by Jahanshahloo et al. (2011), we develop a new ranking method under the condition of variable returns to scale (VRS). Numerical example illustrates the effectiveness of the proposed cross-efficiency based ranking method and demonstrates the advantages of our proposal, against the other ranking approaches.